GAGASAN KONSTITUSI EKONOMI INDONESIA DALAM KERANGKA PASAL 33 UUD 1945 - Johan Erwin Isharyanto (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
The implementation of the principle of economic democracy in Indonesia requires the Government to give an equal portion not only to the private economy and the running government but also to the economy (property) of the people who have sovereignty. So it takes good will, partisanship and legal politics to make cooperatives run well. Cooperatives still color in Indonesia, but only a few are implementing the principles and identity of cooperatives correctly, this must be a control so that there are no actors in the economy acting under the guise of cooperatives. The function of facilitators and regulators from the state is needed by making legal products that are suitable for social welfare goals. Thus based on the Elucidation of Article 33 paragraph (1) of the 1945 Constitution, until now the cooperative is one of the role models of popular economy with the principle of kinship. The government is in the forefront to design the rule of law, as the basis for implementing democratic cooperation, the government will also play a role in stabilizing business competition between private companies, state companies and cooperatives. In other words the government acts as a regulator and facilitator in strengthening the economy in accordance with the mandate of the constitution, with an orientation towards economic independence. Chapter XIV Article 33 and Article 34 of the 1945 Constitution concerning the National Economy and People's Welfare. became the basic postulate of Indonesia's economic constitution.